Perancangan Kebutuhan Jaringan Wifi Untuk Mendukung Proses Belajar Mengajar Pada Universitas Di Era 4.0 - Mudofar Baehaqi; Arifudin Arifudin (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2019)
Technological developments are so rapid in various fields, one of which is in the field of education. Nowadays we can get information, news, knowledge with the internet. In education, increasing knowledge is very important, with the internet we can get the latest scientific knowledge information from journals, modules, digital books from various parts of the world with just a gatget or laptop. To support these activities, it must be with good technology infrastructure, if the ratio between users and infrastructure is not balanced, conges will occur, where the available bandwidth cannot cover users who are connected to the internet, resulting in slow connections. Currently the WIFI network infrastructure at the University of 17 August 1945 Cirebon needs additional access points and additional bandwidth, because when user is connected to WIFI network increase conges occur, and there are several places that are far from the access point location. in network design there are two modeling were used that calculation of bandwidth capacity based on the number of users with three scenarios aksess speed of 0.5 Mbps, 1 Mbps, 2 Mbps and spacious area. The results obtained from modeling based on user capacity, the required access speed of 141.2 Mbps, 282 Mbps and 565 Mbps.The results obtained are calculated based on the user's capacity, the number of access points is 25 Ap and 14 Ap on the calculation based on the area.